2007
DOI: 10.1021/jp070745s
|View full text |Cite
|
Sign up to set email alerts
|

Surface Patch Binding Induced Intermolecular Complexation and Phase Separation in Aqueous Solutions of Similarly Charged Gelatin−Chitosan Molecules

Abstract: The formation of selective surface patch binding induced complex coacervates between polyions, chitosan (cationic polyelectrolyte), and alkali-processed gelatin (polyampholyte), both carrying similar net charge, was investigated for two volumetric mixing ratios: r = [chitosan]/[gelatin] = 1:5 and 1:10. Formation of soluble intermolecular complexes between gelatin and chitosan molecules was observed in a narrow range of pH, though these biopolymers had the same kind of net charge, which was evidenced from elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 48 publications
(104 reference statements)
3
50
0
Order By: Relevance
“…Figure 3 implies that as coacervation point is reached, the zeta potential of the aggregates that are formed due to associative interactions tends to a very low value indicating effective charge neutralization achieved due to strong electrostatic binding between oppositely charged segments of the polymer. In fact, occurrence of turbidity maxima coincides with minimum zeta potential which is in complete agreement with the requirement dictated by models of phase transition [11]. The experimental data indicate the interplay of at least two different types of interactions that precede coacervation:…”
Section: Solvent Polaritysupporting
confidence: 85%
See 3 more Smart Citations
“…Figure 3 implies that as coacervation point is reached, the zeta potential of the aggregates that are formed due to associative interactions tends to a very low value indicating effective charge neutralization achieved due to strong electrostatic binding between oppositely charged segments of the polymer. In fact, occurrence of turbidity maxima coincides with minimum zeta potential which is in complete agreement with the requirement dictated by models of phase transition [11]. The experimental data indicate the interplay of at least two different types of interactions that precede coacervation:…”
Section: Solvent Polaritysupporting
confidence: 85%
“…In a small class of systems liquid-liquid phase separation gets initiated by surface selective patch binding [11,18,19] even though both the polyions carry similar net charge. This is often referred to as binding on the wrong side of pH.…”
Section: Surface Patch Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of mechanical characterization can give insight into the molecular-level interactions present in the material, and is critical to enable effective processing of these materials. Generally, coacervates have been reported to have a Newtonian, or a shear-rate independent viscosity [71,111,171,172], as well as a shear thinning response [2,87,111,124,[171][172][173][174][175], depending on the shear rate. The occurrence of shear thinning is suggestive of a structural change in the material, and research has suggested that the tendency for shear thinning in coacervate-based materials may correlate with the strength of the underlying electrostatic interactions [2,174].…”
Section: Viscositymentioning
confidence: 99%